2018
DOI: 10.4184/asj.2018.12.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography- and Radiography-Based Morphometric Analysis of the Lateral Mass of the Subaxial Cervical Spine in the Indian Population

Abstract: Study DesignThis was a double-blinded cross-sectional study, which obtained no financial support for the research.PurposeTo obtain a detailed morphometry of the lateral mass of the subaxial cervical spine.Overview of LiteratureThe literature offers little data on the dimensions of the lateral mass of the subaxial cervical spine.MethodsWe assessed axial, sagittal, and coronal computed tomography (CT) cuts and anteroposterior and lateral X-rays of the lateral mass of the subaxial cervical spine of 104 patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…The results showed that MLD and height increased, and FJA decreased gradually from C3 to C7, indicating that the lateral mass gradually became wide, tall, and steep from C3 to C7. Although the measurement method in this study was different from those conducted by Patil et al and Abdulla et al, the regularity of changes from C3 to C7 in results is similar with theirs 18,21 . We found that the morphology of subaxial lateral masses was similar, enabling one series of prostheses can meet the need of the majority of clinical practice.…”
Section: Accepted Manuscriptsupporting
confidence: 71%
See 2 more Smart Citations
“…The results showed that MLD and height increased, and FJA decreased gradually from C3 to C7, indicating that the lateral mass gradually became wide, tall, and steep from C3 to C7. Although the measurement method in this study was different from those conducted by Patil et al and Abdulla et al, the regularity of changes from C3 to C7 in results is similar with theirs 18,21 . We found that the morphology of subaxial lateral masses was similar, enabling one series of prostheses can meet the need of the majority of clinical practice.…”
Section: Accepted Manuscriptsupporting
confidence: 71%
“…Although the measurement method in this study was different from those conducted by Patil et al and Abdullah et al, the changes from C3 to C7 are similar with theirs. 18,21 We found that the overall morphology of subaxial lateral masses is quite uniform. Thus, one set of prostheses could meet the need of the majority of the patients in clinical practice.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…[ 14 , 15 ] Previous research has found that the relationships between the cervical dura- sac thickness, narrowed spinal canal, and cervical lateral masses are closely associated with disc aging, degeneration, and CCS. [ 16 ] Kayalioglu et al have reported that the pedicles of cervical vertebrae are strong structural anatomic elements of the cervical vertebrae and offer the strength of attachment to the cervical spine. [ 10 ] Wasinpongwanich et al noted that overall mean pedicle height was 6.9 mm at C6.…”
Section: Discussionmentioning
confidence: 99%
“…In the sagittal plane, the pedicle is located on the most rostral quarter (zone 1) of the vertebral body [ Figure 1b ]. [ 3 4 ]…”
Section: Introductionmentioning
confidence: 99%